The effects of service quality dimensions on students' satisfaction: Hedperf model adoption / Siti Rapidah Omar Ali ... [et al.] - Omar Ali, Siti Rapidah; Md Shariff, Nor Alesha; Mohd Said, Nur Shafini; Mat, Khalid Amin (Universiti Teknologi MARA, Perlis, 2020)
Service quality has become one of the greatest imperative factors of students' satisfaction in higher education industry these days. As the education sector is primarily considered service providing establishment, the service quality aspects are the key to sustainable competitive advantage. This study aims to determine the relationship between service quality aspects namely academic aspects, non- academic aspects and reputation towards students' satisfaction. The HEDPERF model was used as a research framework. A set of 265 questionnaires were distributed to the undergraduate students in a public university in the East Coast of Malaysia by using stratified random sampling. A total of 260 of the questionnaires were returned equivalent to 95.84%. The data were analyzed using descriptive statistical analysis, Pearson Correlation and Multiple Regression. The findings revealed that all three dimensions of service quality have a positive relationship with the students' satisfaction. Academic aspect revealed to be the most significant influence towards the students' satisfaction. Suggestion to the management of higher education also been made particularly in the areas where improvement is required.